Strategic Research on the Urban Natural Gas Energy System Under the Path to Ecological Civilization: Fuyang City Case Study - Hao, Yun-li; Li, Shuang; Xia, Qing (Frontiers in Energy Research, 2020)
To help meet the strategic development needs of urban energy systems today and reduce carbon emissions, natural gas can play a pivotal transition role, especially in a country such as China, which has relied very heavily on coal for decades. Though making significant progress toward the maximum possible use of clean, renewable forms of energy, such as hydro, thermal, solar, and wind power, it will take a long time before China can completely abandon the use of fossil fuels. In this paper, using Fuyang City in Anhui Province as a case study, a four-dimensional differential equation model, based on the consumption, price, economic growth, and “ecological civilization construction” of natural gas energy, is developed, which incorporates concepts and calculations of natural gas energy intensity, “natural gas ecological civilization intensity,” and “economic ecological civilization intensity.” It is the first attempt ever made to quantify the construction of urban ecological civilization and discuss the evolutionary relationship among the internal variables of the system. Regression analysis, data fitting, neural network, and other methods are used to confirm the parameters of the system model. Through Matlab simulation of each variable and using an evolution map, a quantitative understanding of the role of natural gas is generated. The research findings reveal that paying attention to the environmental aspects of energy consumption is beneficial to economic growth. The paper concludes that, at present, the best ways for China to reduce its carbon emissions are to implement a market price and peak–valley prices for natural gas, improve the tiered price mechanism, appropriately reduce the economic growth rate, continue to adjust the industrial structure away from heavy industry, and scientifically manage the natural gas energy system. These reforms are of great practical significance in working toward a sustainable development path for the city.